2023
DOI: 10.1155/2023/6374874
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Immunity Gap: A Six-Year Laboratory Data Review of Hepatitis B Serological Profiles in Gauteng Province, South Africa

Abstract: Background. In 1995, the hepatitis B vaccine in South Africa was incorporated into the childhood expanded programme of immunization. We report on immunity gaps of laboratory-based hepatitis B virus (HBV) among patients in public facilities in Gauteng Province from 1st January 2014 to 31st December 2019. Methodology. We analyzed HBV serological data extracted from the National Health Laboratory Services Central Data Warehouse (NHLS CDW). A descriptive analysis was performed for hepatitis B surface antigen (HBsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…[9] Universal HBV vaccination, as part of the EPI, given to children at 6, 10 and 14 weeks of age and at 18 months since 1995, has resulted in a significantly lower prevalence of chronic hepatitis B in subsequent birth cohorts: from 8/622 (1.29%) born before 1995 to 0/572 (0%) in a study of pregnant women from the Western Cape Province and from 7.4% to <4.1% in birth cohorts born before or after 1995 [10] in a large laboratory-based study of >100 000 samples from Gauteng Province. [11] A national measles rash surveillance study showed that only 0.4% of residual samples from children from the post-1995 birth cohort had evidence of current HBV. [12] In an investigation of low-risk blood donors, the prevalence of HBV was 0.84% in samples in individuals born before 1995, decreasing to 0.14% in individuals born after 1995.…”
mentioning
confidence: 99%
“…[9] Universal HBV vaccination, as part of the EPI, given to children at 6, 10 and 14 weeks of age and at 18 months since 1995, has resulted in a significantly lower prevalence of chronic hepatitis B in subsequent birth cohorts: from 8/622 (1.29%) born before 1995 to 0/572 (0%) in a study of pregnant women from the Western Cape Province and from 7.4% to <4.1% in birth cohorts born before or after 1995 [10] in a large laboratory-based study of >100 000 samples from Gauteng Province. [11] A national measles rash surveillance study showed that only 0.4% of residual samples from children from the post-1995 birth cohort had evidence of current HBV. [12] In an investigation of low-risk blood donors, the prevalence of HBV was 0.84% in samples in individuals born before 1995, decreasing to 0.14% in individuals born after 1995.…”
mentioning
confidence: 99%